1986
DOI: 10.1111/j.1432-1033.1986.tb09680.x
|View full text |Cite
|
Sign up to set email alerts
|

The antigenic determinants recognized by three monoclonal antibodies to keratan sulphate involve sulphated hepta- or larger oligosaccharides of the poly(N-acetyllactosamine) series

Abstract: The carbohydrate determinants of keratan sulphate recognized by three monoclonal antibodies (5-D-4, 1-B-4 and MZ15) have been investigated by solid-phase radioimmunoassay using bovine corneal keratan sulphate as the immobilized reference antigen. The antibodies appeared highly specific for sulphated poly(N-acetyllactosamine) sequences, for their binding was strongly inhibited by preparations of keratan sulphate, but not by glycoproteins with non-sulphated poly(N-acetyllactosamine) sequences of I and i antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(134 citation statements)
references
References 33 publications
(21 reference statements)
3
130
1
Order By: Relevance
“…Previously, we found comparatively low levels of sulfated KS in normal mouse cornea based on immunoreactivity with 5D4 (22), a mAb that recognizes high sulfated sequences of residues (minimally penta-sulfated) on poly N-acetyllactosamine disaccharides of KS (23,24). In the current study these KS epitopes were detected in extracts of WT and heterozygous corneas, but not in corneal extracts from homozygous Chst5-null mice (Fig.…”
Section: Resultssupporting
confidence: 50%
“…Previously, we found comparatively low levels of sulfated KS in normal mouse cornea based on immunoreactivity with 5D4 (22), a mAb that recognizes high sulfated sequences of residues (minimally penta-sulfated) on poly N-acetyllactosamine disaccharides of KS (23,24). In the current study these KS epitopes were detected in extracts of WT and heterozygous corneas, but not in corneal extracts from homozygous Chst5-null mice (Fig.…”
Section: Resultssupporting
confidence: 50%
“…After reduction and alkylation, analysis using dot-blots (see below) showed that the G1 preparation reacted with MAb 12/21/1-C-6 (to a common peptide epitope in both the G1 and G2 domains of the core protein [21]), 9/30/8-A-4 (to a peptide epitope present in link protein [17]), and 1/20/5-D-4 (to oligosaccharides from keratan sulfate consisting of several repeats of the disulfated disaccharide GlcNAc[6-sulfate] pl-3 Gal[6-sulfate] pl-4 [23]). This fraction did not react with MAb 5/6/3-B-3 (to terminal unsaturated chondroitin-6-sulfate disaccharides [17]), which indicated that the G1 preparation contained mainly G1, with some link protein present.…”
Section: Methodsmentioning
confidence: 99%
“…Under normal culture conditions, SV40-transformed human corneal epithelial cells do not produce detectable levels of highly sulfated KS GAG, which is recognized by the 5D4 monoclonal antibody (28,29). However, the corneal cells began producing 5D4-positive, highly sulfated KS carbohydrate when CGn6ST and KSG6ST were overexpressed (Fig.…”
Section: Tablementioning
confidence: 99%